Al-Fitnah Al-Kubra Roots Sectarianism In Islam - Rahmadhani, Febri (El-Ghiroh : Jurnal Studi Keislaman, 2024)
The assassination of Uthman was the starting point for the emergence of divisions among Muslims. The incident of al-Fitnah al-Kubra became a dark record that tarnished the glorious history of this Ummah. In the midst of this crisis, Ali tried to fix the situation. However, Ali ascended the throne at an inopportune time. The short-lived and busy government stabilized the state of the state. Civil wars such as Jamal's war and Shiffin's war are also inevitable. This research is a review of existing literature (library research). Library research is a literature review, either from books, notes, or research relevant to this research. The results concluded The schism widened when Ali's dispute with Mu'awiya was ended through tahkim. In fact, it gets worse. If the wound of Muslims with the death of Uthman is likened to the scratch of a dagger, So the wounds of the people, after being caused by various events afterwards, were not only slit but also chopped. So the people seemed to be a pile of meat divided by hungry wolves. Not only that, each group of wolves attacks each other to take the other. To understand the complexity of this condition, the author tries to explain the roots of sectarianism in the bodies of Muslims.